Lectin immunohistochemical evaluation of human bladder carcinomas. A comparison of Carnoy's and formalin fixation - Okamura, T (Hinyokika kiyo. Acta urologica Japonica, 1993)
A lectin immunohistochemical analysis of 51 human bladder carcinomas, including 44 cases of transitional cell carcinoma (TCC) (G1, 15 cases; G2, 17 cases; G3, 12 cases) and 7 cases of squamous cell carcinoma (SCC), was performed. Tissues were obtained by cold punch biopsies, fixed in Carnoy's or 10% formalin solution, stained for binding of 10 different lectins, and evaluated under the light microscope. The lectins used were concanavalin agglutinin (Con A), soybean agglutinin (SBA), Lotus tetragonolobus agglutinin (LTA), Dolichos biflorusa agglutinin (DBA), peanut agglutinin (PNA), Ricinus communis agglutinin I (RCA1), Ulex europaeus agglutinin I, II (UEA-I, II), wheat germ agglutinin (WGA), and Pisum sativum agglutinin (PEA). TCC prepared with Carnoy's fixation tended to show moderately positive Con A, UEA-I, and WGA reactions for G1, and strongly positive reactions for G2 and G3 lesions. UEA-II was mainly negative in G1, but tended to increase to become moderate in G3. DBA tended to show a moderately positive reaction in G1 and G2, but was mainly negative in G3. With formalin fixation, only RCA1 demonstrated grade specific variation, tendency to react moderately in the G1 and G2 cases, and strongly in G3. There were no further differences among the histopathological grades of TCC for other lectins. Thus, Carnoy's fixation appears superior for distinguishing between grades of lesions. SCC tended to react more strongly than TCC with all the various lectins except PEA, independent of fixation